Persistent barrage firing in cortical interneurons can be induced in vivo and may be important for the suppression of epileptiform activity - Suzuki, Norimitsu; Tang, Clara S.; Bekkers, John M. (Frontiers in Cellular Neuroscience, 2014)
Neural circuits are typically maintained in a state of dynamic equilibrium by balanced synaptic excitation and inhibition. However, brain regions that are particularly susceptible to epilepsy may have evolved additional specialized mechanisms for inhibiting overexcitation. Here we identify one such possible mechanism in the cerebral cortex and hippocampus of mice. Recently it was reported that some types of GABAergic interneurons can slowly integrate excitatory inputs until eventually they fire persistently in the absence of the original stimulus. This property, called persistent firing or retroaxonal barrage firing, is of unknown physiological importance. We show that two common types of interneurons in cortical regions, neurogliaform cells and fast-spiking multipolar cells, are unique in exhibiting barrage firing in acute slices ( 85% and 23% success rate for induction, respectively). Barrage firing can also be induced in vivo, although the success rate for induction is lower ( 60% in neurogliaform cells). In slices, barrage firing could reliably be triggered by trains of excitatory synaptic input, as well as by exposure to proconvulsant bath solutions (elevated extracellular K+, blockade of GABAA receptors). Using pair recordings in slices, we confirmed that barrage-firing neurogliaform cells can produce synaptic inhibition of nearby pyramidal neurons, and that this inhibition outlasts the original excitation. The ubiquity of neurogliaform and fast-spiking cells, together with their ability to fire persistently following excessive excitation, suggests that these interneurons may function as cortical sentinels, imposing an activity-dependent brake on undesirable neuronal hyperexcitability.